Derived Pali and Sanskrit Words Written in Thawa Thossamas Royal Ceremony Poem A Writing by Her Royal Highness Princess Maha Mala Krom Phraya Bumrab Porrapak. - Likithdamrongkiat, Weerapong; Chaipunya, Chittapa Sarapadnuke (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
This qualitative study aims to introduce the study of the sources, changes of forms, and classification of derived Pali and Sanskrit words written in Thawa Thossamas Royal Ceremony Poem, a writing by Her Royal Highness Princess Maha Mala Krom Phraya Bumrab Porrapak, Fine Arts Department Copy. It was published in 2545 of Buddhist Era. The findings indicated that the derived Pali and Sanskrit words written in Thawa Thossamas Royal Ceremony Poem, a writing by Her Royal Highness Princess Maha Mala Krom Phraya Bumrab Porrapak has the 124 words of derived words from Pali language, 154 words of derived words from Sanskrit language, 135 words of derived words from Pali and Sanskrit languages, 278 words of compound words between Pali and Sanskrit languages and 49 words from Pali and Sanskrit words that were created and used in Thai language, 743 words all of this. There are 3 aspects of derived words adaptation are 1. Cutting words, including cutting of vowels, cutting words consonants and cutting of syllables. 2. Adding words, including adding of vowels, adding of consonants, adding of tone marks, adding of syllables, and adding any punctuations. 3. Change words form, including change form of vowels, change form of consonants and change of Nikahit vowel mark. And classified derived words from Pali and Sanskrit words into 12 groups of phrases , including human and organs, properties, verbs, unhuman and gods, places, animals and plants, natural resources, stars and date/time, subjects, religions and beliefs, objects and weapons and counting numbers phrases. Derived Pali and Sanskrit Words, Thawa Thossamas Royal Ceremony Poem